POWER AND CONSEQUENCES SYMBOLISM IN FRANKENSTEIN - Perdiansyah, Rifky Ali; Afghani, Muhammad Al; Taufik, Elza Salsabillah Arriyaha Lawaqih; Nurholis, Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This paper discusses the use of symbolism in Mary Shelley’s Frankenstein, illustrates how Shelley uses various symbols as a form of social criticism of the moral degradation when scientific exploration is separated from ethical considerations. Through several symbols, the novel highlighting the dangers of ambition uncontrolled by moral limitations. The symbol that show on the monster, represent dangerous consequences of uncontrolled scientific ambition. Victor Frankenstein, as the creator, crosses moral and ethical boundaries by creating life without considering his responsibilities. Also, the nature elements that Shelley uses is shown as an example how the quest for knowledge can lead to disaster, warning readers of the moral responsibility that comes with science. This study explores how the novel uses symbols to reflects concept of man and the responsibility of the creator emphasize how important it is to consider the moral and social implications of every action.